2016
DOI: 10.1002/iub.1469
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐derived mesenchymal stem cells modulate the immune response in chronic experimental autoimmune encephalomyelitis model

Abstract: Multiple sclerosis (MS) is an autoimmune inflammatory neurodegenerative disease of the central nervous system (CNS) that disrupts the myelin sheath, leading to dysfunction of the brain and spinal cord. No curative treatment is known for MS. Mesenchymal stem cells, through their immunomodulatory effects, represent a promising therapeutic approach for MS. The aim of this article is to explore the impact of human adiposederived mesenchymal stem cells (ASCs) on chronic experimental autoimmune encephalomyelitis (EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 41 publications
0
24
0
2
Order By: Relevance
“…Using hBM‐MSCs, Bai et al showed a decrease in leukocyte infiltration into the CNS and enhanced a Th2 cytokine profile, but also enhanced oligodendrogenesis, suggesting that hBM‐MSCs affect immunomodulation but also enhanced neuronal repair . Similar results showing a Th2 cytokine shift and enhanced oligodendrogenesis were reported using hA‐MSCs and using human decidua‐derived MSCs (hD‐MSCs) . hA‐MSCs were also shown to express the immunosuppressive gene human leukocyte antigen G (HLA‐G) and to induce the secretion of the anti‐inflammatory protein TNF‐α‐stimulated gene/protein 6 following culture with inflammatory cytokines .…”
Section: Immunomodulation and Neuroinflammationmentioning
confidence: 67%
See 1 more Smart Citation
“…Using hBM‐MSCs, Bai et al showed a decrease in leukocyte infiltration into the CNS and enhanced a Th2 cytokine profile, but also enhanced oligodendrogenesis, suggesting that hBM‐MSCs affect immunomodulation but also enhanced neuronal repair . Similar results showing a Th2 cytokine shift and enhanced oligodendrogenesis were reported using hA‐MSCs and using human decidua‐derived MSCs (hD‐MSCs) . hA‐MSCs were also shown to express the immunosuppressive gene human leukocyte antigen G (HLA‐G) and to induce the secretion of the anti‐inflammatory protein TNF‐α‐stimulated gene/protein 6 following culture with inflammatory cytokines .…”
Section: Immunomodulation and Neuroinflammationmentioning
confidence: 67%
“…Similar results showing a Th2 cytokine shift and enhanced oligodendrogenesis were reported using hA‐MSCs and using human decidua‐derived MSCs (hD‐MSCs) . hA‐MSCs were also shown to express the immunosuppressive gene human leukocyte antigen G (HLA‐G) and to induce the secretion of the anti‐inflammatory protein TNF‐α‐stimulated gene/protein 6 following culture with inflammatory cytokines . Payne et al tested the effect of hA‐MSCs ex vivo modified to over‐express the anti‐inflammatory ILs‐4 and −10 in EAE mice.…”
Section: Immunomodulation and Neuroinflammationmentioning
confidence: 68%
“…Therefore, it seems that although AD-MSCs are cultured and expanded in vitro under standard condition, the donor's status could influence their properties by altering inflammatory profile. Shalaby et al (2016) established that the transplantation of human AD-MSCs taken from lipoaspirate from the subcutaneous white adipose tissue of healthy donors had beneficial effects on chronic EAE rats. In detail, AD-MSCs (1 × 10 6 ) injected intravenously improved clinical disease score and reduced B-cell, macrophage, and T-cell infiltration in brain, as well as vascular congestion and axonal loss of the gray and white matters of cerebral cortex.…”
Section: Adipose-derived Mscsmentioning
confidence: 99%
“…Brains and lymph nodes of EAE rats treated with AdMSCs show a significant expression of human leukocyte antigen G (HLA-G) gene. The immunomodulatory effects of AdMSCs may be related to their secretion of HLA-G (73). Engineering of AdMSCs as carriers for IFN-β delivery, or secretors of IL-10, has shown beneficial effects in experimental models of MS (74,75).…”
Section: Adipose-derived Mscsmentioning
confidence: 99%